1999
DOI: 10.1097/00005768-199908000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Performance and muscle fiber adaptations to creatine supplementation and heavy resistance training

Abstract: Creatine supplementation enhanced fat-free mass, physical performance, and muscle morphology in response to heavy resistance training, presumably mediated via higher quality training sessions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
181
1
21

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(217 citation statements)
references
References 27 publications
14
181
1
21
Order By: Relevance
“…Although syringeal muscle fiber diameters do scale positively with body mass (Figure 5), there is little comparative data to suggest that this is a trend across muscles in a variety of species. Furthermore, it is well known that testosterone can increase muscle fiber sizes up to 50% (e.g., Volek et al 1999, Sinha-Hikim et al 2002 as can resistance training with protein supplementation (Andersen et al 2005). Although male superfast fibers tended to be larger than those of females in all cases, this difference was only significant in Zebra Finch and Bengalese Finch.…”
Section: Discussionmentioning
confidence: 91%
“…Although syringeal muscle fiber diameters do scale positively with body mass (Figure 5), there is little comparative data to suggest that this is a trend across muscles in a variety of species. Furthermore, it is well known that testosterone can increase muscle fiber sizes up to 50% (e.g., Volek et al 1999, Sinha-Hikim et al 2002 as can resistance training with protein supplementation (Andersen et al 2005). Although male superfast fibers tended to be larger than those of females in all cases, this difference was only significant in Zebra Finch and Bengalese Finch.…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown to be effective in enhancing strength and power performance and increasing lean body mass (25,31,33). Most studies examining creatine supplementation generally employed a week-long loading phase (20 gÁd 21 ) followed by daily maintenance doses (5 gÁd 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…A classic CR research study reported an increase in strength performance following 12 weeks of supplementation when combined with heavy resistance training (80% one repetition maximum) [34]. In this study, participants ingested 25 g/day CR for seven days (loading phase), followed by 5 g/day CR for the remainder of the study (maintenance phase).…”
Section: Creatine and Strength Trainingmentioning
confidence: 94%